The influence of institutional and contingency factors on the adoption of forensic accounting by anti-corruption agencies: A proposed framework - Umar, Ibrahim; Samsudin, Rose Shamsiah; Mohamed, Mudzamir (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
The increasing concern over corruption in developing countries has been associated with the inability of Anti-Corruption Agencies (ACAs) to tackle corruption. The ineffectiveness of these ACAs is said to be influenced by several factors including the underutilization of forensic accounting in fraud investigation process. This article focuses on the identification of these factors and their influences on the adoption of forensic accounting by ACAs. This was done through the review of literature and proposing a framework for further in-depth research work. The conceptual framework highlights the antecedent influence of political will on these factors and their influences on the adoption of forensic accounting. The implication is that identifying these factors through further in-depth studies will contribute to the insufficient research work on the adoption of forensic accounting and help policy makers to enhance the performance of these agencies.